(3OjhGf SYOGdOjf Hf YQHjs - (3eMeO Hf eMeO Hf Ydj Hf YQHj GdWGFj GdMGJej, SYO GdOjf , J (B656 (3g` s
(3ChdgG (B:s
(3Yai Gddg Yf Yjfjc ce SacJ OekG hce ahbJ fMh GdLhGfM CSgekG s
(3BNQgG (B:s
(3adCUHQf Ydi LaGg aQHeG aGR GdeJje HGdhUGd HUHQg s
(3GSJcJHgG dfaSg eMeO Cejf Hf eMeO SYjO GdGSWhGfj GdOeTbj SfI (B1296s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B257s
Keywords: (3GdCOHs